(untitled) (Annals of Medical Research, 2021)
Aim: Total laparoscopic hysterectomy has several advantages compared to laparotomy including shorter hospitalization, faster recovery time, less pain, and less hemorrhage. Our aim was to determine the relationship between patient-specific/surgery-related variables and operation times in this study. Materials and Methods: We recruited 191 patients who underwent total laparoscopic hysterectomy. We compared variables including uterine volume, surgical suture materials, and body mass index with operation time. The study was performed with the permission of the Training Plan and Coordination Board Committee of our institution (18/06/2019- No: 10).Results: The uterine volume and body mass index of the patient did not influence the operation time whereas the suturing technique by the laparoscopic approach substantially affected the operating time (p=0.902, p=0.117 and p=0.012, respectively). There was a statistically significant difference between suture type and operation time. The cases that used barbed sutures required a shorter operation time. Conclusion: We investigated the relationship between interesting entities such as uterine volume, type of suture material, and operation times. Laparoscopy should be performed widely in suitable cases. The type of suture material provided an important difference in the operation.